2004
DOI: 10.1158/0008-5472.can-03-2284
|View full text |Cite
|
Sign up to set email alerts
|

Role of p12CDK2-AP1 in Transforming Growth Factor-β1-Mediated Growth Suppression

Abstract: p12CDK2-AP1 (p12) is a growth suppressor isolated from normal keratinocytes. Ectopic expression of p12 in squamous carcinoma cells reversed the malignant phenotype of these cells, in part due an ability of p12 to bind to both DNA polymerase ␣/primase and to cyclin-dependent kinase 2 (CDK2), thereby inhibiting their activities. We report in this article that in normal epithelial cells, transforming growth factor ␤1 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 42 publications
2
43
0
2
Order By: Relevance
“…We have also found that p12 CDK2-AP1 mediates TGF-binduced growth inhibition (Hu et al, 2004). A recent report shows that p12 CDK2-AP1 expression levels are differentially downregulated in microsatellite-unstable colorectal cancer cell lines compared to microsatellitestable cell lines (Yuan et al, 2003).…”
Section: Introductionsupporting
confidence: 67%
“…We have also found that p12 CDK2-AP1 mediates TGF-binduced growth inhibition (Hu et al, 2004). A recent report shows that p12 CDK2-AP1 expression levels are differentially downregulated in microsatellite-unstable colorectal cancer cell lines compared to microsatellitestable cell lines (Yuan et al, 2003).…”
Section: Introductionsupporting
confidence: 67%
“…To gain insight into the molecular and biochemical alterations resulting through Cdk2ap1 knock-out, we examined phenotypic and biochemical changes in vitro by using Cdk2ap1 Ϫ/Ϫ mESC clones. Based on the known effect of CDK2AP1 on CDK2 activity and pRb phosphorylation and previous findings on CDK2 activity and pRb phosphorylation in mESCs, we hypothesized that CDK2AP1 has a functional role in the differentiation competency of mESCs (15,23). As shown in Fig.…”
Section: Altered Differentiation Competency In Cdk2ap1mentioning
confidence: 85%
“…1). TGF-β1 treatment of normal human keratinocytes increased cellular levels of CDK2AP1 mRNA and protein (Hu et al, 2004). Analysis of the data suggests that SMAD induced by TGF-β1 binds at the proximal promoter of the CDK2AP1 gene.…”
Section: Cdk2ap1 In Cancersmentioning
confidence: 94%